2013
DOI: 10.7554/elife.00523
|View full text |Cite|
|
Sign up to set email alerts
|

Passive and active DNA methylation and the interplay with genetic variation in gene regulation

Abstract: DNA methylation is an essential epigenetic mark whose role in gene regulation and its dependency on genomic sequence and environment are not fully understood. In this study we provide novel insights into the mechanistic relationships between genetic variation, DNA methylation and transcriptome sequencing data in three different cell-types of the GenCord human population cohort. We find that the association between DNA methylation and gene expression variation among individuals are likely due to different mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

46
447
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 412 publications
(495 citation statements)
references
References 57 publications
46
447
2
Order By: Relevance
“…To date, the potential relationships between DNA methylation and gene expression have only been systematically analyzed in a small subset of studies (Gevaert, Tibshirani & Plevritis, 2015; Gutierrez‐Arcelus et al., 2013, 2015), and the potential effects of these relationships on aging and cancer are yet to be elucidated. To this end, we explored the establishment of potential correlations between these two processes using the TCGA‐KIRC dataset.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the potential relationships between DNA methylation and gene expression have only been systematically analyzed in a small subset of studies (Gevaert, Tibshirani & Plevritis, 2015; Gutierrez‐Arcelus et al., 2013, 2015), and the potential effects of these relationships on aging and cancer are yet to be elucidated. To this end, we explored the establishment of potential correlations between these two processes using the TCGA‐KIRC dataset.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variation has been shown to contribute to longevity, evidenced by the fact that longevity runs in families (Schoenmaker et al ., 2006). Clear relationships also exist between DNA methylation and genetic variability, and recent studies have identified genetic loci whose variation is strongly associated with DNA methylation at nearby sites (Fraser et al ., 2012; Gamazon et al ., 2013; Gutierrez Arcelus et al ., 2013; Moen et al ., 2013). Thus, it is possible that genetic variants associated with longevity may also be correlated with DNA methylation changes.…”
Section: Considerations For Studies Of Epigenetics and Agingmentioning
confidence: 99%
“…Approximately 60–70% of genes have a CpG island associated with their promoters, and promoters can be classified according to their CpG density (Saxonov et al ., 2006; Weber et al ., 2007). Levels of DNA methylation at a promoter‐associated CpG island are generally negatively associated with gene expression, although some specific genes show the opposite effect (Weber et al ., 2007; Lam et al ., 2012; Gutierrez Arcelus et al ., 2013). Interestingly, this negative correlation is not upheld when comparing expression and DNA methylation for a specific gene across individuals (van Eijk et al ., 2012; Lam et al ., 2012; Gutierrez Arcelus et al ., 2013; Wagner et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations